Significance Of The Concept “Human Existence” In Existentialism In Forming A Set Of Values For Youngsters In Vietnam Nowadays - Hue, Nguyen Thi Nhu (IJRDO - Journal of Social Science and Humanities Research, 2019)
Although there are some limitations, overestimating personal values and trivializing social values, in the concept of “human existence” in existentialism, it certainly makes each human think of his status and natural values that we, intentionally or unintentionally, have lost or forgotten, so that we would be creative and have our own special thinking. On that basis, the paper draws significance of forming a set of values for youngsters in Vietnam currently. That is orienting on building life purposes, training optimistic, activeness, creativity, and motivations for each person; Orienting on combining traditional values and creative values; Orienting on building the balance personal values and social values; Orienting on building love towards work.